Local Wisdom-based Computational Thinking Diagnostic Test: A Bibliometric Analysis Mapping State-of-the-Art and Research Gaps - Reny Refitaningsih Peby Ria; Dyah Susilowati (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This research aims to prove the novelty of research related to the implementation of diagnostic tests to improve computational thinking skills based on local wisdom using bibliometric analysis. This type of research uses qualitative descriptive research. The data collection technique uses secondary data in the form of literature from the Google Scholar database. Data analysis uses bibliometric analysis with the help of VOSviewer software. The results of this study indicate that the topics of Computational Thinking, Diagnostic Test, and Local Wisdom have not been found research with these topics, so there are opportunities for research by collaborating topics.